HfO2‐CoO nanoparticles for electrochemical dopamine sensing. Issue 1 (4th May 2021) - Butt, Abdul Samad; Baig, Nadeem; Khan, Munezza; Ul‐Hamid, Anwar; Sher, Muhammad; Altaf, Muhammad; Sohail, Manzar
Abstract: Dopamine (DA) is a neurotransmitter that plays a pivotal role in the brain's proper functioning and several other physiological processes. Herein, we demonstrate the miniaturized electrochemical sensor for detecting DA using hafnium metal‐organic framework (Hf‐MOF) derived new nanocomposite of hafnium and cobalt oxides (HfO2 ‐CoO). Calcination of Hf‐MOF coated with cobalt acetylacetonate complex [(Co(acac)2 ] yield HfO2 ‐CoO nanoparticles supported over in situ generated graphitic carbon. The excellent adsorption capabilities of HfO2 and highly catalytic CoO activity make this bimetallic HfO2 ‐CoO nanocomposite to display a stable response over a wide linear concentration range when used as electrode material in the electrochemical DA sensing process. Moreover, the computational study also proves that CoO improves the chemisorption properties of HfO2 for DA. Electrochemical studies are performed through cyclic voltammetry (CV), linear sweep voltammetry (LSV), and differential pulse voltammetry (DPV). For the case of LSV, the HfO2 ‐CoO nanocomposite modified glassy carbon electrode (HfO2 ‐CoO/GCE) exhibit a linear response to DA concentration ranging from 0.25 to 3.15 mM. However, with DPV HfO2 ‐CoO/GCE electrode has displayed a linear range of 10–190 μM and a detection limit of 1.8 μM is achieved. The electrode has also shown excellent stability, and only 19 % loss in its initial current response is observed over 150 days of specific interval testing. The HfO2 ‐CoO/GCE nanocomposite electrode, due to its unique feature of stability, selectivity, and sensitivity, has a good potential for use as an analytical tool for non‐enzymatic sensing of DA and other neurotransmitters in the human fluid. Abstract :